Anmeldelser - Jacobsen, Niels Kingo; Jensen, Ruth Helkiær (Geografisk Tidsskrift, 1967)
Litteraturanmeldelser: FYSISK GEOGRAFI m. m. Pekeris: Geophysical Theory and Computers (K. H.) ................... 281 Landsberg & Van Mieghem: Advances in Geophysics (S. R.) .............. 284 Geophysik und Geologie, Folge 9 (K. H.) ................................ 281 Krinov: Giant Meteorites (K. H.) ....................................... 282 Paulmann: Zur Festigkeits-Anisotropie von Gesteinen (K. H.) .......... 281 Metz: Lehrbuch der Tektonischen Geologie (K. H.) ....................... 282 Brinkmann: Abriss der Geologie, I: Allgemeine Geologie (K. H.) ........ 282 Gunzert: Salzfolge u. Bau der Kalisalz-Lagerstätte von Stebnik (K. H.) . . . . 281 Wilcoxson: Volcanoes (N. N.) ............................................ 294 Yatsu: Rock Control in Geomorphology (N. N.) .......................... 294 Weber: Die Oberflächenformen des festen Landes (N. N.) .............. 294 Marsal: Statistische Methoden f. Erdwissenschaftler (R. H. J.) .......... 325 Simakova: Soil Mapping By Color Aerial Photography (N. K. J.) ........ 283 Held & Glawson: Soil Conservation in Perspective (N. K. J.) ............ 283 Morgan: Governing Soil Conservation (N. K. J.) .......................... 283 Bunce: The Economics of Soil Conservation (N. K. J.) ................... 283 de Bakker & Schelling: Bodemclassificatie voor Nederland (N. K. J.) ..... 292 Shul’gin: The Temperature Regime of Soils (N. K. J.) ................... 294 Felitsiant: Capillary Movement of Water and Salt Solutions (N. K. J.) . . . . 294 Davis & DeWiest: Hydrogeology (S. R.) ................................. 285 Bruce & Clark: Introduction to Hydrometeorology (S. R.) .............. 284 Apollov, Kalinin & Komarov: Hydrological Forecasting (S. R.) .......... 285 Knopf & Cook: Marine Sciences Instrumentation (N. N.) .............. 297 Miller: The Sea (N. N.) .................................................. 298 McCormac: Aurora and Airglow (B. F.) ................................... 298 Proceedings, International Conference on Permafrost (B. F.) ............ 299 Day: The Science of Weather (Kr. M. J.) ................................. 311 Hendl: Klimakunde der deutschen Landschaften (Kr. M. J.) .............. 311 Rudloff: Die Schwankungen des Klimas in Europa (Kr. M. J.) ........ 311 Pogosyan: The Air Envelope of the Earth (Kr. M. J.) ................... 312 Steinhäuser: Probleme der Wettervorhersage (Kr. M. J.) ................. 312 Middleton: A History of the Thermometer (Kr. M. J.) ................... 312 Problémes Météorol. de la Stratosphere et de la Mesosphere (Kr. M. J.) ... . 313 KARTOGRAFI m. m. Albrecht: Formeln u. Hilfstafeln f. Geogr. Ortsbestimmungen (B. F.) . ... 328 Hammond: Air Survey in Economic Development (R. H. J.) .............. 290 Witt: Thematische Kartographie (R. H. J.) .............................. 290 Imhof: International Yearbook of Cartography, VI (N. N.) ............ 296 Stamp: A Glossary of Geographical Terms (N. N.) ..................... 296 Lana, lasbez & Meak: Glossary of Geographical Names (N. N.) .......... 297 KULTUR- OG ERHVERVSGEOGRAFI Galtung: Theory and Methods of Social Research (R ,H. J.) .............. 292 de Hcusch: A la découverte des Tsiganes (N. N.) ....................... 301 Doerr/Uehlinger: Spezielle patologische Anatomie (C. G. F.) .......... 317 Meyer, Kain & Wohl: The Urban Transportation Problem (P. K.) ........ 317 Tinbergen: Grundlagen der Entwicklungsplanung (P. K.) ................. 318 Chapin: Urban Land Use Planning (P. K.) .............................. 318 Alonso: Location and Land Use (P. K.) .................................. 319 Lösch: The Economics of Location (P. K.) .............................. 319 Chardonnet: Géographie industrielle, II (V. H.) ......................... 303 Opencast Mining, Quarrying and Alluvial Mining (K. H.) ................. 283 Wilsie: Crop Adaption and Distribution (N. K. J.) ..................... 284 Symons: Agricultural Geography (V. H.) ................................ 286 Herre: Das Ren als Haustier (N. K. J.) .................................. 301 Roepke: Readings in Economic Geography (V. H.) ....................... 303 Obst: Allgemeine Wirtschafts- und Verkehrsgeographie (R. H. J.) ........ 304 Ritter: Planning for Man and Motor (P. K.) ............................ 313 Otremba & Kessler: Viehwirtschaft im Agrarraum der Erde (R. H. J.) . . . . 315 Andreae: Weidewirtschaft im südlichen Afrika (R. H. J.) .............. 316 George, Guglielmo, Kayser & Lacoste: La Géographie Active (R. H. J.) . .. . 316 Research on Road Traffic (P. K.) ......................................... 317 EUROPA OG SOVJETUNIONEN Kvalheim: Geochemical Prospecting in Fennoscandia (K. H.) ............ 292 Sömme: Die Nordischen Länder (N. N.) ................................ 312 Proctor: Ancient Scandinavia (E. S.) ..................................... 323 Oslo Byplankontor: Transportanalysen for Oslo-området (P. K.) ........ 324 Dovring: Land and Labor in Europe in the 20th Century (V. H.) ..... 302 Freeman, Rodgers & Kinvig: Lancashire, Cheshire and the Isle of Man (V. H.) .................................................................. 286 Gutersohn: Jura (V. H.) .................................................. 287 Gutersohn: Alpen, 1. Teil (V. H.) ......................................... 287 Liepolt: Limnologie der Donau (K. H.) ................................ 322 Walker: A Geography of Italy (Aa. Aa.) ................................ 287 FREMMEDE VERDENSDELE Ali: The Emergence of Pakistan (S. F.) ................................ 306 Dempster: Japan Advances (S. Chr.) ....................................... 306 Dichter: The North-West Frontier of West Pakistan (S. F.) .............. 306 Liu & Yeh: The Economy of the Chinese Mainland (S. Chr.) ............ 307 Kirby: Contemporary China (S. Chr.) ..................................... 307 Koentjaraningrat: Villages in Indonesia (S. F.) .......................... 307 Geertz: The Social History of an Indonesian Town (S. Chr.) ............ 308 Önnerfors: Hystoria Tartarorum C. de Bridia Monachi (I. R. K.) ........ 322 Cahen & Snelling: The Geochronology of Equatorial Africa (K. H.) ...... 282 Buser: Paleostructures of Nigeria and Adjacent Countries (K. H.) ........ 282 Kanter: Libyen (Aa. Aa.) ................................................ 288 Schiffers: Heinrich Barth. Ein Forscher in Afrika (N. N.) .............. 304 Brander: The River Nile (V. H.) ....................................... 305 The Middle East and North Africa 1965-66 (Aa. Aa.) ................... 305 Seek & Mondjannagni: L’Afrique occidentale (H. J.) ................... 305 Davies: West Africa before the Europeans (N. Noe-N.) ................. 310 Widstrand: Afrikaresenärer. En Antologi (C. G. F.) ....................... 314 Mary: Afrika-Schrifttum, Vol. I (C. G. F.) ................................ 320 Gusinde: Von gelben und schwarzen Buschmännern (M. R.) .............. 321 Kilby: African Enterprise: The Nigerian Bread Industry (H. J.) .......... 325 Carlson: Africa’s Ilands and Nations (H. J.) .............................. 326 Nørregård: Danish Settlements in West Africa 1658-1850 (H. J.) .......... 327 Lloyd, Mabogunje & Awe: The City of Ibadan (H. J.) ................... 328 Thompson: Geography of New York State (V. H.) ..................... 288 Schwerin: Oil and Steel (Aa. Aa.) ....................................... 289 Maybury-Lewis: Akwe-Shavante Society (H. J.) .......................... 326 Beals: Community in Transition: Nayön - Ecuador (Aa. Aa.) ............ 290 Vest & Augelli: Middle America: Its Lands and Peoples (V. H.) ........ 309 Lyle & Caiman: Statistical Abstract of Latin America 1965 (Aa. Aa.) . ... 309 Hopkins: The Bering Land Bridge (B. F.) ................................ 299 Boe: The Journal and Letters of Capt. Ch. Bishop (C. G. F.) .............. 315 POLAREGNENE Hoel: Svalbard III (B. F.) ................................................ 300 Wilson: Diary of the DISCOVERY Expedition (B. F.) ................... 299 Ray: Eskimo Masks: Art and Ceremony (B. F.) .......................... 300 Gad: Grønlands Historie, I (B. F.) ....................................... 320 Rubin: Studies in Antarctic Meteorology (B. F.) .......................... 321 Amer. Geogr. Soc.: Terrestrial Life of Antarctica (B. F.) .............. 321 Kosack: Die Polarforschung (B. F.) ..................................... 329 ATLASVÆRKER OG KORT Bodemkaart van Nederland, Blad 43 West, Willemstad (N. K. J.) ........ 293 Bodemkaart van Nederland (N. K. J.) ..................................... 293 Neuer Atlas der Welt (N. N.) ........................................... 295 Oxford Regional Economic Atlas: United States & Canada (V. H.) . ... 308 Oxford Regional Economic Atlas: Africa (P. K.) .......................... 316 The Shorter Oxford Economic Atlas of the World, 3. udg. (P. K.) ........ 316 Herrmann: An historical atlas of China (C. G. F.) ..................... 313 Atlas der Schweiz, 1., 2. & 3. Lieferung (N. N.) ............................ 323 LÆREBØGER Trewartha, Robinson & Hammond, Elements of Geogr., 5. udg. (R. H. J.) 291 Long & Roberson: Teaching Geography (R. H. J.) ....................... 291 Lambert: The Teaching of Ecology (S. Chr.) ............................ 315 BØGER INDGÅET TIL REDAKTIONEN .......................... 330 Geografforeningen..................................... 331